Pain after lower limb amputations: insights from the Heidelberg amputation registry - Nees, Timo A.; Matt, Cornelia; Deisenhofer, Julian; Block, Julia; Wolf, Sebastian Immanuel; Renkawitz, Tobias; Lehner, Burkhard; Alimusaj, Merkur (Medicina, 2024)
Background and Objectives: The experience of unpleasant sensory phenomena after lower limb amputations (LLAs), including phantom limb pain (PLP), phantom limb sensation (PLS), and residual limb pain (RLP), impacts global healthcare and adversely affects outcomes post-amputation. This study aimed to describe the distribution of PLP, PLS, and RLP among patients with LLAs registered in the Heidelberg Amputation Registry. The primary objective was to determine the prevalence of sensory abnormalities across different amputation levels and causes. Materials and Methods: In this single-center, cross-sectional study, data from 459 patients registered in the Heidelberg Amputation Registry were analyzed for the occurrence of PLP, PLS and RLP. Subsequently, logistic regression models were used to identify the independent risk factors associated with sensory disturbances following LLAs. The mean age of the LLA patients (31% female, 69% male) was 58 years (SD ± 18). Results: The patients were, on average, 44 years old (SD ± 22) at the time of amputation, with a mean duration since amputation of 15 years (SD ± 17). Transtibial amputations were the most common (43%), followed by transfemoral (39%) and partial foot amputations (10%). Hip and knee disarticulations were observed in 3.7% and 3.5% of the cohort, respectively, with hemipelvectomies accounting for 1%. Traumatic injuries (32%) and neoplastic disorders (22%) were the leading causes of LLAs, while peripheral artery disease and diabetes were responsible for 12% and 6% of cases, respectively. Importantly, a significant proportion of participants (85%) reported experiencing abnormal sensations. The prevalence rates for phantom limb pain (PLP), phantom limb sensation (PLS), and residual limb pain (RLP) were 58%, 66%, and 46%, respectively. The occurrence of sensory disturbances, with the exception of RLP, was significantly affected by the level of amputation. Notably, the age at amputation emerged as an independent risk factor for developing abnormal sensations, including PLS. Conclusions: In conclusion, this study provides a comprehensive overview of sensory abnormalities in a diverse cohort of LLA patients, highlighting the age at amputation as an important factor. The findings emphasize the role of comprehensive registries in enhancing care for individuals with amputations and guiding targeted pain management strategies.
Gesehen am 19.05.2025